Knowledge and use of isotretinoin in Saudi female college students: Cross -sectional study - Thuraya Ahmed Albadr; Danah Khalid Alruhaimi; Peter M B. Cahusac; Dileep Kumar Rohra (Journal of Dermatology and Dermatologic Surgery, 2019)
Background: The most effective treatment for severe acne is isotretinoin. However, it carries major side effects, such as teratogenicity, depression, and increased lipid profiles. It is advised to monitor the lipid profile and to use two forms of contraception during isotretinoin use. Although it is commonly prescribed, little data are available regarding patients' understanding of isotretinoin. Objectives: The aim of this study is to assess Saudi female college students' knowledge about isotretinoin use and side effects. Methods: Data were collected by a validated online questionnaire disseminated through social media, allowing the collection of information from students from different regions of the country. Results: The total number of responses was 622. The majority of respondents were 18–24 years old, single, and college students; all were female. About 48.6% (282) of the sample used isotretinoin. Most had good knowledge of isotretinoin side effects. Medical students were more knowledgeable than students of other majors, and users were more knowledgeable than nonusers. The most common side effect was dryness. Use among married females was 2.8%, the majority of whom were instructed by their physicians to use only one method of contraception. One respondent got pregnant while using the drug. Conclusion: College-aged females generally have good knowledge of isotretinoin and its side effects. However, awareness about proper contraceptive use while on the drug is lacking.